PERAN SALES MARKETING DI HOTEL ROYAL ASNOF PEKANBARU - Maisurya Eristina; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to determine the implementation of sales marketing responsibility in an effort to increase revenue at the Royal Asnof Hotel Pekanbaru. This study uses a qualitative method with a qualitative descriptive approach to describe and explain the situation that occurs by collecting data and information in the field. The key informants in this research are the sales marketing manager and the accounting chip. In this study, the data collection techniques used were interviews, observation and documentation. Based on the results of the study, it can be concluded that the sales marketing task of the Royal Asnof hotel Pekanbaru has been carried out in almost all things that refer to the theory used. Keywords: implementation, Sales Marketing.